ANALISIS KEPUASAN WISATAWAN TERHADAP VARIASI PAKET DENPASAR CITY TOUR - Shintia Jayanti; I Wayan Suardana; I Made Kusuma Negara (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2014)
Denpasar city tour as one of tourism product in Bali, also developed becomes one of favorite choice for tourist. Since tourism industry product is very dynamic and depends on the environment, it is important to know tourist’s perception and analysis about tourist satisfaction for variety of Denpasar city tour, for making some regulation to improve the product or making some innovation about the product. This research conducted by questionnaire method, also supported with interviews and direct observation. The results analyzed by using Importance-Performance Analysis. The result showed that tourist felt dissatisfaction about the product (Denpasar city tour) as shown at the indicator (92,75 percent), and cartecius diagram showed that there are some point that is important for the tourist and should be maintain the performance, such as variation object, facility in the object, reliable information. There are also some point that tourist feel it is important but they feel dissatisfaction about it. There are security checks and security staffs in the object.